Ethnic disparity in financial fragility in Malaysia - Abdullah Yusof, Selamah (Emerald Group Publishing Ltd., 2019)
Purpose – The purpose of this paper is to investigate the extent of financial fragility and its disparity across ethnic groups in Malaysia. Disparities related to income and wealth are major concerns as they breed conflict and social instability. The study also compares the level of financial fragility of Malaysians with their neighboring Asian counterparts. Design/methodology/approach – This study uses the World Values Survey to construct two financial fragility measures. Descriptive analysis is used to compare the level of financial fragility of Malaysia with other Asian countries. Ordinary least squares and generalized ordered logit regressions are applied to determine the existence of ethnic disparity in financial fragility in Malaysia. Findings – There exist ethnic differences in financial vulnerability in Malaysia where Malay and Indian are in a more financially fragile situation compared to Chinese. Other socio-economic factors and character trait also impact financial fragility. Compared to neighboring countries, the level of financial fragility in Malaysia is low. Nevertheless, over 40 percent of the Malaysians are just getting by in terms of their expenditure relative to income. They may be at risk to financial shocks without adequate savings or funds. Social implications – Ethnic disparity in financial vulnerability added to the inequality in income and wealth can pose a serious threat to Malaysia which attempts to achieve long-lasting social harmony and sustainable development. Originality/value – This is the first study that attempts to compare the level of individual financial fragility across Asian countries. It also makes use of a larger scale survey and a more representative sample to examine ethnic disparity in financial fragility in Malaysia. In addition, character trait is included in the analysis to provide a better understanding of human behavior in affecting financial outcomes.